PENGARUH KEPEMILIKAN PUBLIK, PERTUMBUHAN PERUSAHAAN, DAN UKURAN KANTOR AKUNTAN PUBLIK TERHADAP PENGGANTIAN AUDITOR - Kristian, Michelle (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2015)
The issue of auditor’s independence is the main cause why the company is required to conduct mandatory penggantian auditor. Various questions arise when there are companies that perform voluntary penggantian auditor, the change of auditors outside thePeraturan Menteri Keuangan No. 17/PMK.01/2008. The purpose of this study is to test the effect of public ownership, company’s growth, and public accountant firm’s size towards penggantian auditor. The object of this study is Kompas100 Index company for period 2011-2013. Selection of the sample is determined based on purposive sampling method. The sample used in the study are 34 companies that are successively entered Kompas100 Index period 2011-2013 except for the financial sector, presenting financial statements in Indonesian Rupiah, has assets increased from year to year, and contains all data related to all variables. The data used in this study are secondary data, the annual financial statements audited by an independent auditor. Data analysis method used is logistic regression, as the dependent variable is non-metric and the independent variables are mixture of metric and non-metric. The results of this study are (1) public ownership does not affect penggantian auditor significantly, (2) company’s growth does not affect penggantian auditor significantly, (3) public accountant firm’s size does not affect penggantian auditor significantly, (4) public ownership, company’s growth, and public accountant firm’s size simultaneously do not affect penggantian auditor significantly.